Research progress and evolution prospect of passive internet of things communication - Yuan LI; Yulu ZHANG; Yu DING; Shuai MA; Shanpeng XIAO; Jianming XIAO; Jian LI (物联网学报)
Passive internet of things (IoT) is the fundamentally enabling technology of promoting digital transformation and upgrading of industries.In recent years, passive IoT communication technology such as radio frequency identification has been widely used in asset management fields due to its advantages of low cost, zero power consumption, and easy deployment.In this context, passive IoT communication technology and the latest research progress were introduced, the potential evolution prospects of passive IoT were analyzed.Based on that, development bottlenecks and challenges of passive IoT communication were given, a novel passive IoT communication system with deep fusion of the cellular system was presented, and the key technology research directions of this field were proposed.It is aimed to inspire new thoughts for the development of passive IoT communication technology.